Continuity and Discontinuity in Learning Careers Potentials for a Learning Space in a Changing World - Merrill, Barbara; Galimberti, Andrea; Nizinska, Adrianna; González-Monteagudo, José (Research on the Education and Learning of Adults, 2018)
Continuity and Discontinuity in Learning Careers: Potentials for a Learning Space in a Changing World focuses on the continuities and discontinuities of the learning careers and identities of non-traditional adult students in diverse learning contexts. Readership: All those interested in adult education and the challenges facing adult education today such as researchers in education and social sciences, undergraduate and postgraduate students, policy-makers and practitioners.